(untitled) (Research, Society and Development, 2022)
The study aimed to analyze adherence to measures to combat COVID-19 in the state of Paraná in the first year of the pandemic. This was a cross-sectional, descriptive research with a quantitative approach, carried out from March 2020 to March 2021 in 64 municipalities in Paraná, drawn by uniform stratified sampling according to territorial classification and political-administrative division into corresponding Health Regions (HR). Data collection was documented through municipal transparency portals. The variables analyzed were the restrictive measures and release measures adopted to deal with COVID-19. Most normative documents (64.49%) contained restriction measures, published mainly by urban municipalities (40%), and the 10th and 8th were the regions with the highest frequency of measures. The adoption of release measures was uneven among the municipalities, reflecting the limited national governance. It is hoped that the results of the study can contribute to the reflection on the posture of municipal entities in the face of the governance adopted in the COVID-19 pandemic, as well as the role of Union coordination in this context. Forthermore, to enable the organization of coping policies for future health crises.